O autoritarismo em questão: um estudo de caso sobre o ensino de História e a Ditadura Militar Brasileira na Escola de Aplicação da UFPA - CUNHA, Gabriel da Silva (Universidade Federal do Pará, 2023)
This work aims to discuss the concept of authoritarianism and how it mobilizes issues such as revisionism and denialism about the Brazilian military dictatorship. To achieve this objective, a case study was carried out with the history professors of the School of Application of the Federal University of Pará, an institution chosen as the locus of research due to the difficulties arising from the new coronavirus pandemic. The research also analyzes how these narratives are present in different environments and how they present themselves in their workplace, in addition to discussing the different resources and strategies that can be used by teachers in teaching about the Brazilian military dictatorship. As a product, a blog was created, with posts built from the analysis of bibliographic references, experiences reported by the participating teachers and the analysis of internet pages dedicated to providing resources about the Brazilian military dictatorship.